2015
DOI: 10.1039/c5ra11099h
|View full text |Cite
|
Sign up to set email alerts
|

A facile and general synthesis strategy to doped TiO2 nanoaggregates with a mesoporous structure and comparable property

Abstract: A facile and general route was explored to fabricate porous metal-doped TiO 2 nanoaggregates from titanium glycolate precursor and metal salts, and the doping with Co or Ni is an effective approach to improve the photocatalytic efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 38 publications
(70 reference statements)
2
17
0
Order By: Relevance
“…4b showed the plot of (αhv) 2 versus photon energy (hv) for the as-prepared composites and pure Bi 2 WO 6 , where α, h, and v are the absorption coefficient, constant, and light frequency, respectively. 34,35 The energy of the band gap is calculated by extrapolating the straight line to the abscissa axis. The band gap of the pure Bi 2 WO 6 was estimated to 2.89 eV.…”
Section: Xps Analysismentioning
confidence: 99%
“…4b showed the plot of (αhv) 2 versus photon energy (hv) for the as-prepared composites and pure Bi 2 WO 6 , where α, h, and v are the absorption coefficient, constant, and light frequency, respectively. 34,35 The energy of the band gap is calculated by extrapolating the straight line to the abscissa axis. The band gap of the pure Bi 2 WO 6 was estimated to 2.89 eV.…”
Section: Xps Analysismentioning
confidence: 99%
“…The sharp absorption edge of pristine TiO 2 can be detected at ∼392 nm, corresponding to the intrinsic large band gap energy of 3.16 eV, and a similar result was also observed in the previous report. 47 The UV−vis diffuse reflectance spectrum of bluish-green Ni(HCO 3 ) 2 is different from those of conventional semiconductor photocatalysts. It displays three regions of absorption edges under light irradiation wavelengths from 200 to 800 nm, and a similar phenomenon was also observed by Parida et al 48 It was found the absorption edge could be divided into three parts: from 200 to 300 nm, from 300 to 500 nm, and from 500 to 800 nm.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Photocurrent response and EIS were widely used to investigate separation efficiency and charge‐transfer capability of the photoinduced electron and holes in the photocatalyst during the photocatalysis reaction [22, 25]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All the experiments were carried out in a standard three‐electrode cells containing 0.5 mol/l Sodium Sulfate (Na 2 SO 4 ) aqueous solution with a platinum foil and a saturated calomel electrode as the counter electrode and the reference electrode [22]. The working electrode was prepared according to the following process: 20 mg of as‐prepared sample was mixed with 1 ml of N, N‐Dimethylformamide (DMF) and 0.01 ml of nafion solution (5%, DuPont) to form homogeneous ink.…”
Section: Methodsmentioning
confidence: 99%